Women's preferences for cervical cancer screening: a study using a discrete choice experiment. - Wordsworth, S; Ryan, M; Skåtun, D; Waugh, N (2006)
OBJECTIVES: Recent policy recommendations for cervical screening include liquid-based cytology. This new approach could improve laboratory throughput, reducing the waiting time for test results. New guidelines also standardize the interval for screening, with women aged 25-50 offered screening every 3 years and women aged 50-64 every 5 years. Quantitative evidence on the preferences of women for alternative screening programs is limited; this study, therefore, elicits such preferences. METHODS: A postal questionnaire using a discrete choice experiment was mailed to 2,000 women in the Tayside Health Board region of Scotland. RESULTS: A response rate of 44 percent from those women who had previously had a smear was achieved. Women had a significant positive preference for reductions in recall rates and waiting time for results. Women preferred more frequent screening, particularly those aged 50+. Expected reductions in the chance of recall from the conventional Pap smear to the new liquid-based cytology were associated with a willingness to pay of pound 41. Women aged 50+ would be willing to pay pound 42 to increase the frequency of screening from every 5 to every 3 years. Service characteristics did not influence screening participation. CONCLUSIONS: Guidance to move to liquid-based cytology will meet women's preferences for fewer repeat cervical smears and should reduce waiting time for results. However, proposals to increase screening intervals for those aged 50+ are inconsistent with the preferences for this age group. From a policy perspective, our study results suggest that the changes in attributes of the service such as unsatisfactory smear rates and frequency of screening, will improve service efficiency without affecting participation rates.